(untitled) (Bangladesh Journal of Botany, 2015)
The chemical composition of the essential oil obtained from N. sativa was analyzed by GC/MS and the components identified were: p-cymene (22.05%) followed by ?-thujene (6%), ?-pinene (1.11%), camphene (11%), sabinene (1%), ?-pinene (7%), ?-myrcene (0.21%), ?-phellandrene (0.45%), limonene (0.13), ?-terpinene (5.12%), terpinolene (0.23%), camphor (1%), carvone (0.32%), thymoquinone (20.32%), thymol (10.12%), carvacrol (10%), longicyclene (0.9%) and borneol (0.43). The oils were also subjected to screening for their possible antioxidant activity by using 2,2-diphenyl-1-picrylhydrazyl (DPPH) assays. Thymol (13.0 ± 0.8 ?g/ml), thymoquinone (12.6 ± 0.0 ?g/ml) and carvacrol (12.03 ± 0.0 ?g/ml) showed appreciable antioxidant activity in DPPH test. Antioxidant activity guided fractionation of the oil was carried out by the TLC-bioautography screening and fractionation resulted in the separation of the main antioxidant compound which were identified as thymoquinone (51%), thymol (25%) and carvacrol (8%). DOI: http://dx.doi.org/10.3329/bjb.v44i1.22732 Bangladesh J. Bot. 44(1): 111-116, 2015 (March)